Study of the pathological changes induced by irradiated protoscolices (from sheep hydatid cysts ) after intra peritoneal injection in white male mice - Faleh, Enaam Bader; Majeed, Saleh Kadhim; Al - Bayati, Ahmed Jassim (The Iraqi Journal of Veterinary Medicine, 2004)
In the present study , we investigate the effect of Gamma radiation of wavelength 81.58416X10^-13 on the viability of protoscolices , the larval stage of Echinococcus granulosus , which was isolated from liver hydatid cysts of invested sheep. The study was accomplished on 80 white male mice , the mice were divided randomly into four equal groups , group 3 and 4 were invested intra peritoneally with 2000 Gamma irradiated protoscolices, with 5 and 25 Gray of Gamma rays for 1.2 and 6.6 minutes respectively The experimental irradiation of protoscolices was Gamma rays cobalt 60 ( Co-60 ). Then the ability of protoscolices was checked before and after the irradiation. Group 1 and group 2 were used as negative and positive control respectively. After one month group 2 , 3 and 4 were given challenge dose of 2000 protoscolices intraperitoneally for every single mouse in every group. Mice were killed after 2,4,6,8, and 12 weeks after the challenge . Macroscopic and microscopic studies were done for all experimental groups. The following findings were seen : 1. Reduction of the violability of protoscolices by inverse of the radiation intensity incorrespondense with the time of exposure. 2. The macroscopic studies indicate reduction in the average number and diameter of the secondary hydatid cyst in the irradiated groups in comparison with the positive group. 3. The histopathological changes were characterized by presence of degenerated distracted hydatid cysts in the livers , especially in the irradiated group , with the presence of hyperplastic splenic white pulp lymphoid tissue in comparison with the positive control .